FRAGMENTASI mtDNA MAMBRUK CRISTATA DAN VICTORIA OLEH BEBERAPA ENZIM RESTRIKSI: Fragmentation of mtDNA of Goura cristata and victoria by some Restriction Enzymes - Agust Kilmaskossu (FMIPA Universitas Papua, 2009)
The difference between Goura cristata and Goura Victoria could be distinguished by comparison of the morphology characters than the internal factors. Internal factors such as genetics characters are required in certain cases to distinguish the bird species. Therefore, a study on the mtDNA of the birds has been done. Three restriction enzymes have been used to produce fragmentation of mtDNA of the birds and analysis the differences between them. One of the three enzymes, RsaI, shows a difference in the fragment mtDNA; and could be used as a marker in differentiation of bird species especially in the Goura species.